Pengaruh modifikasi menu makanan lunak terhadap tingkat kepuasan pasien dan sisa makanan di Rumah Sakit Umum Daerah Meuraxa Banda Aceh - Cut Sri Mutia; Rachmawati Rachmawati (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Soft foods are foods with a texture that is easy to chew, swallow, digest than regular food. The purpose of administration is to be easily swallowed and digested according to nutritional needs and disease conditions. Modification of recipes is very important to improve the appearance in shape, taste, color, aroma, and temperature of food so that it can be well received by patients.Objectives: The aim was to determine the effect of soft food modification on the level of patient satisfaction and food waste at the Meuraxa General Hospital in Banda Aceh City.Methods: Quasi-experimental research design. This research was conducted at Meuraxa Public Hospital in Banda Aceh City. Which will be carried out from November to December 2018. The population in this study is all inpatients at the Meuraxa general hospital in Banda Aceh city from November to December receiving soft diets. The sample in this study was carried out using the purposive sampling technique in which the sample taken in the Arrahman Room and Arafat Room. Quantitative data analysis with an independent sample t-test was performed to compare food scraps before modification and after modifications to the soft food menu, the data presentation was presented in tabular and narrative form.Results: The rest of the food on the 3rd menu after statistical tests using the t-test can be concluded that there is a significant influence between the remaining rice on the modification of soft foods before and after modification (p < 0.05). Soft food scraps on the 4th menu showed a significant effect between vegetable residues on modified soft foods before and after they were modified (p < 0.05). Soft food residues on the 5th menu before and after modification also showed a significant effect between vegetable residues on modification of soft foods before and after modification (p < 0.05).Conclusion: Modifications to the menu on soft foods showed a significant influence on the level of patient satisfaction and food waste at the Meuraxa District General Hospital in Banda Aceh. Suggestions, modification of soft food menu can be used as an alternative dish that can be served to inpatients.